Kepentingan Nasional Ethiopia Dalam Pembangunan Kembali Angkatan Laut Ethiopia Pada Tahun 2018-2019 (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
Ethiopia is a landlocked country. Due to these geographical conditions, Ethiopia cannot get easy access to the sea, but policy makers in Ethiopia decided to build a Navy for their country. This decision taken in 2018 is a unique case to study according to the author. This study then attempts to analyze the reasons for the development of the Ethiopian Navy. The framework of thinking used as the basis for this research is the concept of national interest, more specifically basic interests proposed by Hans. J. Morgenthau and Donald E. Nuechterlein. This study was analyzed using a qualitative methodology using secondary data sources. This research then finds the answer that the reason for Ethiopia to build a Navy is because there are several basic interests behind the decision, that is security interest, security interest and world order interest.